2014
DOI: 10.1016/j.celrep.2014.04.026
|View full text |Cite
|
Sign up to set email alerts
|

MLKL Compromises Plasma Membrane Integrity by Binding to Phosphatidylinositol Phosphates

Abstract: Although mixed lineage kinase domain-like (MLKL) protein has emerged as a specific and crucial protein for necroptosis induction, how MLKL transduces the death signal remains poorly understood. Here, we demonstrate that the full four-helical bundle domain (4HBD) in the N-terminal region of MLKL is required and sufficient to induce its oligomerization and trigger cell death. Moreover, we found that a patch of positively charged amino acids on the surface of the 4HBD binds to phosphatidylinositol phosphates (PIP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
659
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 695 publications
(697 citation statements)
references
References 36 publications
12
659
0
2
Order By: Relevance
“…Recent work has demonstrated that recruitment of MLKL to RIP3 and MLKL phosphorylation results in the conformational change that leads to the exposure of its four‐helix bundle domain (FHBD) and oligomerization of MLKL (Murphy et al , 2013). Binding of the FHBD to negatively charged phosphatidylinositol phosphates has been proposed to recruit MLKL to the plasma membrane allowing it to directly permeabilize the membrane by forming a pore (Dondelinger et al , 2014; Su et al , 2014; Wang et al , 2014). Alternatively, it has been also proposed that plasma membrane‐bound MLKL recruits Ca 2+ or Na + ion channels to permeabilize the membrane (Cai et al , 2014; Chen et al , 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has demonstrated that recruitment of MLKL to RIP3 and MLKL phosphorylation results in the conformational change that leads to the exposure of its four‐helix bundle domain (FHBD) and oligomerization of MLKL (Murphy et al , 2013). Binding of the FHBD to negatively charged phosphatidylinositol phosphates has been proposed to recruit MLKL to the plasma membrane allowing it to directly permeabilize the membrane by forming a pore (Dondelinger et al , 2014; Su et al , 2014; Wang et al , 2014). Alternatively, it has been also proposed that plasma membrane‐bound MLKL recruits Ca 2+ or Na + ion channels to permeabilize the membrane (Cai et al , 2014; Chen et al , 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation of MLKL promotes its oligomerization and translocation to the plasma membrane where it interacts with phospholipids and compromises membrane integrity ultimately resulting in cell rupture. [88][89][90][91] MLKL also promotes the generation of reactive oxygen species (ROS) and late phase activation of JNK. 92 The increased production of ROS, especially by the mitochondria, has been strongly linked with mediating TNFinduced necrosis.…”
Section: Rip1 and Rip3 As Drivers Of Necroptosismentioning
confidence: 99%
“…When apoptosis is blocked, for example, using the pan caspase inhibitor zVAD-fmk, assembly of the 'necrosome' is triggered within the cytosol, a complex formed by receptor-interacting serine/threonine-protein kinase-1 and -3 (RIPK1 and RIPK3, respectively), 24 followed by recruitment and activation of mixed lineage kinase domain-like (MLKL) protein. 25,26 Recently, it has been proposed that during necroptosis, MLKL is translocated to the plasma membrane where it oligomerizes upon interaction with PI(4,5)P 2 and PI(5)P via its N-terminal four helical bundle domain to induce membrane permeabilization 27 (Figure 2c). Interestingly, whether necroptotic, primary necrotic and secondary necrotic cells are recognized by the same phospholipid detector(s) to mediate their removal is unclear.…”
Section: Box 1 Phospholipids As Key Regulators Of Intracellular Procementioning
confidence: 99%
“…Intriguingly, the ability of these plant innate defense molecules to induce membrane permeabilization via binding to inner membrane PI(4,5)P 2 and forming oligomers resembles the aforementioned PI(4,5)P 2 -dependent targeting and oligomerization by MLKL in mammalian cells undergoing necroptosis. 27 It is tempting to speculate that the targeting of PI(4,5)P 2 by both plant defensins and the mammalian MLKL to facilitate membrane disruption may reflect convergent evolutionary pathways in which the primary downstream function is to induce cell lysis through interactions with this key phospholipid. Collectively, the availability of specific phospholipids at the microbial membrane can also operate as a form of phospholipid code and act as a major target of innate antimicrobial peptides.…”
Section: Pathogenic Entry Via the Host Extracellular Phospholipid Codementioning
confidence: 99%